Utilization of an Ethnomathematics-Based Quantum Learning Model in Elementary Schools for the Realization of Indonesia’s Sustainable Development Goals (SDGs) - Ach. Eka Hendriawan; Khamiliya Khoirunnisa; Sya’adhatun Ariayah; Hilda Izatun Nafsi; Ni’matur Rohmah; Zaenal Abidin (Universitas Negeri Surabaya, 2025)
Mathematics learning in elementary schools still faces challenges due to students’ low level of understanding, exacerbated by the impact of the pandemic and less varied learning models. This study aims to describe the implementation of ethnomathematics- based Quantum Learning as an innovative strategy to enhance both conceptual understanding and learning motivation. The method employed was descriptive qualitative, using interviews, documentation, and literature studies, with data reduction, presentation, and conclusion drawing as the stages of analysis. The results show that integrating Quantum Learning with local cultural contexts creates a more enjoyable learning atmosphere, increases student participation, and strengthens conceptual understanding of mathematics. Moreover, ethnomathematics provides added value by presenting learning that is closely related to daily life while fostering cultural appreciation. These findings affirm that ethnomathematics-based Quantum Learning can serve as an effective strategy to support quality education in line with the Sustainable Development Goals (SDGs).